Jøden og orientaleren - Thing, Morten (Kvinder, Køn & Forskning, 2000)
This article historizes the terms the "Orient" and "orientals" by using anti-feminist and anti-semitic writing from the 19th century. The Jews were in science and literature portrayed as the "Others" withing Europe, and the author discusses the cultural changes, which are viewed as a critique of nationalism but also as a critique of modernity.